SP10.1.8 Acute uncomplicated diverticulitis: to scope or not to scope?. (9th August 2022) - Howie, Emma; Almafreji, Ibrahim; Cole, Charlotte; Watt, David
Abstract: Aims: To investigate whether endoscopic follow up after a CT proven diagnosis of acute uncomplicated diverticulitis detected additional pathology, specifically colorectal cancer, and if our findings support the European Society of Coloproctology's consensus statement that "a single episode of CT verified uncomplicated diverticulitis endoscopic follow-up remains controversial and may not be necessary". Methods: A retrospective study evaluated every General Surgical emergency admission with acute uncomplicated diverticulitis to our unit in a 5 year period (2015–2020) to assess for radiological diagnosis and endoscopic follow up. Results: Over the 5 years there were 685 admissions with acute uncomplicated diverticulitis affecting 547 individuals. 74.3% of admissions and 80.3% of individuals underwent a Computerised Tomography (CT) during admission. 244 admissions (48%) went on to have an endoscopic examination, with 12.3% of these being inpatient investigations. 50% (122) of patients undergoing endoscopy had confirmed uncomplicated diverticulitis. Of the remaining patients undergoing endoscopy, 79.5% had no pathology detected. Only 1 malignant polyp was discovered on endoscopy with no tumours detected. Conclusions: CT has a high sensitivity and specificity in the diagnosis of acute uncomplicated diverticulitis. We suggest that it is reasonable not to utilise endoscopy as a screening tool after uncomplicated diverticulitis and the risks versus benefits must be carefully considered, especially in the era of Covid-19 where resources are tight and waiting lists ever growing. An endoscopic procedure is a costly, uncomfortable procedure that puts the patient at risk of morbidity and mortality. Our findings support the European Society of Coloproctology's statement regarding endoscopic follow-up.